2021
DOI: 10.1136/bcr-2021-244759
|View full text |Cite
|
Sign up to set email alerts
|

Primary lung abscess due to multidrug-resistantKlebsiella pneumoniae

Abstract: Primary lung abscess as a complication of necrotising community-acquired pneumonia due to multidrug-resistant (MDR) Klebsiella pneumoniae is rare. A 63-year-old man with a medical history of type 2 diabetes mellitus and chronic kidney disease was diagnosed with lung abscess due to MDR Klebsiella pneumoniae, a rare organism as a causative agent for community-acquired pneumonia. This unusual case revealed therapeutic challenges faced owing to factors such as drug-resistant pathogen, longer duration of antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In murine models, HiAlc Kpn long-term infection in the lungs could induce pulmonary fibrosis. Although it has been known that Kpn has become an increasing cause of communityacquired lung abscess 28,29 , Kpn-induced pulmonary fibrosis has been rarely reported 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In murine models, HiAlc Kpn long-term infection in the lungs could induce pulmonary fibrosis. Although it has been known that Kpn has become an increasing cause of communityacquired lung abscess 28,29 , Kpn-induced pulmonary fibrosis has been rarely reported 30 .…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that inadequate antibiotic intensity and duration of treatment administered at local hospitals contributed to the development of multidrug-resistant bacteria. Without the prompt initiation of sensitive antibiotics, the prostate abscess might progress further, potentially leading to the infection of distant organs ( Chrystle et al, 2021 ; Kam et al, 2019 ; Mücke et al, 2017 ). Hence, the judicious selection of sensitive antibiotics, coupled with adequate dosage and duration of treatment, is of paramount importance in the management of prostate abscesses.…”
Section: Discussionmentioning
confidence: 99%
“…The patient underwent insufficient antibiotic intensity and treatment course before attending our medical center. As a result, the development of multi-drug-resistant features of the gram-negative bacilli might contribute to disseminating prostatic abscess to the spleen ( Chrystle et al, 2021 ; Mucke et al, 2017 ). However, blood and urine cultures suggested that amikacin was also a sensitive alternative, in this case, practical usage of carbapenems antibiotics was reported to shorten the postinfection length of stay and benefited the patient eventually ( Zilberberg et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%